REWARD SYSTEM OF SINGLE SALARY AND PERFORMANCE IN THE HIGHER EDUCATION - Hindrayani, Aniek; Muhtar, Muhtar (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2019)
This study aimed to evaluate the performance of employees after the implementation of the remuneration policy to the Higher Education and identify the reward policy and performance patterns with the pattern payroll employee remuneration and employee satisfaction levels. This study uses secondary data from the financial statements and the primary data in the form of interviews using questionnaire with the selected respondents in the sample, the academic staffs who have earned a salary based on the pattern of a single salary. The results showed that the financial performance in the achievement of 90.11% of payroll pattern showed a good indicator, but there are 0.89% of the budget that is not absorbed, which means the percentage of the expected performance can not be achieved. Analysis of the performance behavior indicate that there are changes in the behavior of post-implementation performance of the employee remuneration. Variance test results indicate that there are significant differences in the pattern of implementation of the remuneration in universities in Indonesia, which is indicated by the indicator system and the implementation of remuneration policies